Chiral chromatography and surface chirality of carbon nanoparticles. Issue 12 (11th October 2022) - Hubbard, Misché A.; Luyet, Chloe; Kumar, Prashant; Elvati, Paolo; VanEpps, J. Scott; Violi, Angela; Kotov, Nicholas A.
Abstract: Chiral carbon nanoparticles (CNPs) represent a rapidly evolving area of research for optical and biomedical technologies. Similar to small molecules, applications of CNPs as well as fundamental relationships between their optical activity and structural asymmetry would greatly benefit from their enantioselective separations by chromatography. However, this technique remains in its infancy for chiral carbon and other nanoparticles. The possibility of effective separations using high performance liquid chromatography (HPLC) with chiral stationary phases remains an open question whose answer can also shed light on the components of multiscale chirality of the nanoparticles. Herein, we report a detailed methodology of HPLC for successful separation of chiral CNPs and establish a path for its future optimization. A mobile phase of water/acetonitrile was able to achieve chiral separation of CNPs derived from L‐ and D‐ cysteine denoted as L‐ CNPs and D‐ CNPs. Molecular dynamics simulations show that the teicoplanin‐based stationary phase has a higher affinity for L‐ CNPs than for D‐ CNPs, in agreement with experiments. The experimental and computational findings jointly indicate that chiral centers of chiral CNPs are present at their surface, which is essential for the multiple applications of these chiral nanostructures and equally essential for interactions with biomolecules and circularly polarized photons. Abstract : ….